2021
DOI: 10.3390/w13121695
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trend Analysis of Precipitation and Extreme Events over Kosi River Basin in India

Abstract: Analysis of spatial and temporal changes of long-term precipitation and extreme precipitation distribution at a local scale is very important for the prevention and mitigation of water-related disasters. In the present study, we have analyzed the long-term trend of 116 years (1901–2016) of precipitation and distribution of extreme precipitation index over the Kosi River Basin (KRB), which is one of the frequent flooding rivers of India, using the 0.25° × 0.25° resolution gridded precipitation datasets obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Several studies have provided valuable insights into the spatiotemporal distributions and variability of rainfall within the domain of Indian climatology [5,22]. Recently, India has confronted several excessive rainfall occasions that have led to huge harm to infrastructure and affected the lives of thousands and thousands of people [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have provided valuable insights into the spatiotemporal distributions and variability of rainfall within the domain of Indian climatology [5,22]. Recently, India has confronted several excessive rainfall occasions that have led to huge harm to infrastructure and affected the lives of thousands and thousands of people [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in analyzing precipitation trends have been reported across the world in various river basins such as the Indus basin [47], Vea catchment [48], Awash River basin [49], and Yarlung river basin [40]. Similarly, in India, trend studies using gridded satellite products have been performed in the Kosi River basin [50], the Cauvery basin [51][52][53], and the Gomati basin [54].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, characterizing the spatial distribution of precipitation is crucial for improving the physical understanding of regional climate dynamics and for evaluating weather and climate models, which possibly helps manage water resources and deals with flood crises as well [8][9][10]. In addition, precipitation is a major driving force of hydrological processes and the most active factor in the water cycle [11,12]; small changes in its pattern directly influence such hydrological regime as runoff, soil moisture, and groundwater reserves of concerned regions [13][14][15]. The dynamics of the hydrological simulation models are also influenced to a certain extent by the spatial variability of precipitation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the hydrological simulation models are also influenced to a certain extent by the spatial variability of precipitation [16][17][18]. However, the identification, verification, and quantification of trends in precipitation and its spatial distribution are significant challenges due to significant changes in global climate and the highly spatial and temporal variability of precipitation [7,13,19]. Within complex topography, the characteristic spatial scales of meteorological forcing are typically poorly captured even with a relatively dense network of measurements [18].…”
Section: Introductionmentioning
confidence: 99%